The Influence of Indoor Air Quality on Hospitality Management: Examining Biological, Physical and Economic Factors - O. C. Molua; A. O. Ukpene; J. C. Igborgbor; C. P. Ukpene; J. U. Emagbetere (Journal of Social Responsibility, Tourism and Hospitality, 2023)
This article explores the complex domain of indoor air quality and its significant impact on human health. This study examines the complex relationship between indoor environments and well-being by exploring the interplay of biological factors (e.g., mold and pollutants), physical aspects (e.g., ventilation systems), and the economic implications of investing in home air quality improvements. This article highlights the importance of collaborative research and innovation in addressing the intricate relationship between biology, physics, and home economics to promote healthier living environments. It achieves this by synthesizing existing literature, employing interdisciplinary methodologies, and analyzing outcomes.